Modified docetaxel-cisplatin in combination with capecitabine as first-line treatment in metastatic gastric cancer. a phase II study. - Polyzos, Aristides; Felekouras, Evangellos; Karatzas, Theodore; Griniatsos, John; Dimitroulis, Dimitrios; Polyzos, Kostas; Kontzoglou, Kostas; Mantas, Dimitrios; Karavokyros, John; Nikiteas, Nikolaos; Tsavaris, Nikolas; Syrigos, Kostas; et al. (Anticancer Res, 2012)
The combination of docetaxel, cisplatin and fluorouracil is considered to be one of the reference regimens for advanced gastric cancer, but due to its major myelotoxicity, its use in clinical practice has become limited. This prospective phase II study evaluated the activity and toxicity of a modified regimen with lower doses of docetaxel and cisplatin combined with oral capecitabine instead of fluorouracil for patients with advanced gastric cancer. Treatment consisted of docetaxel at 60 mg/m(2) i.v. followed by cisplatin at 60 mg/m(2), both administered on day one, every three weeks. Capecitabine at 2 g/m(2) per day was administered in two divided doses for 14 days (days 2-15). Thirty six patients were enrolled in the study. The median age was 64 years and performance status (ECOG) was 0-1. All patients had advanced disease, 78% with liver metastases, 100% with intra-abdominal lymph node metastases and 67% with peritoneal implants. Out of the 36 patients, 13 had undergone gastric resection, 13 had received adjuvant chemotherapy with irinotecan-leucovorin-fluorouracil, while seven patients had undergone adjuvant radiotherapy. The remaining 23 patients presented with advanced inoperable disease. Among 36 evaluable for response cases, there were 16 (44.4%) (Confidence Internal (CI) 95%=28-60%), partial responses. Stable disease was recorded in 12 (33.3%), resulting in an overall disease control rate of 78% (CI 95%=69-87%), while 8 (22.3%) patients progressed on chemotherapy. The median response duration was 6 (range=3-8) months. The median time-to-progression was 5 (range=3-6) months and the median survival (after the administration of a second-line chemotherapy in 12 patients), was 12 (range=5-24) months. Myelotoxocity was the main toxicity, with grade 3-4 neutropenia occurring in 18 (50%) and febrile neutropenia in six (16%) patients. Granulocyte-Colony Stimulating Factor (G-CSF) support was given to 16 (44.4%) patients, while grade 3 thrombocytopenia was recorded in two (6%). In conclusion, this modified regimen of docetaxel-cisplatin-capecitabine appears to have comparable efficacy with that reported for the reference regimen, with acceptable toxicity when G-CSF support is provided. However, because due to the small size of the study, further investigation is warranted.
Keywords: Adult; Aged; Antineoplastic Combined Chemotherapy Protocols; Capecitabine; Cisplatin; Deoxycytidine; Female; Fluorouracil; Humans; Lymphatic Metastasis; Male; Middle Aged; Neoplasm Metastasis; Stomach Neoplasms; Taxoids